Kinerja SDM Aparatur Melalui Pelayanan Administrasi di Desa Kemiri Kecamatan Panti Kabupaten Jember - candra w, Aditya; Maulana, Akbar (Indonesian Journal of Public Administration Review, 2023)
Improving the performance of village officials is very important, because recently the performance of many village officials in providing services in the village requires quite a long time. This has an impact on existing services in the village. This research looks at the phenomenon of the stages of human resource development in improving the performance of village officials in terms of administrative services. This research aims to analyze improving the quality of human resource performance of apparatus through administrative services in Kemiri Village, Panti District, Jember Regency. The research method used was descriptive qualitative with data collected through interviews, observation, and documentation from various sources, including the Village Head, Village Secretary, Head of Services, Hamlet Head, and the local community. The research results show that there are three important indicators in developing human resources for officials which are related to improving the quality of performance of village officials, namely determining needs, determining program content, and program implementation. To increase the capacity of village officials, there is training held by the sub-district government every month. However, this training is still less effective because the needs and desires of village officials themselves have not been fully met. In order to improve the quality of human resource performance in Kemiri Village, further action needs to be taken, such as providing rewards for village officials who excel, fixing technical problems in launching online administration services, and optimizing training programs by taking into account the needs and desires of village officials. With these steps, it is hoped that improving the quality of HR performance of Kemiri village officials will be better and more effective.